On local operators diagonal with respect to the system of Hermitian polynomials - Pilipenko, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We present necessary conditions for operators diagonal with respect to the system of Hermitian polynomials to be local.